Analisis Nilai Pendidikan Karakter Sosial dalam Buku Siswa K-13 Akidah Akhlak Kelas V MI - Anisa, Nur Islamiatul; Amri, Muhammad; Syamsudduha, St.; Damayanti, Eka; Salahuddin (Al Asma: Journal of Islamic Education, 2023)
This study aims to describe the material, learning steps, and evaluation sheets of students in the book K-13 moral creed class V publishers of the Directorate of KSKK Madrasah Directorate General of Islamic Education Ministry of 2020. This research uses a qualitative research type with content analysis techniques and semiotic, sociological, theology, and pedagogy. Using primary and secondary data sources. The research method is documentation in the form of books and other documents. Data processing techniques; coding, classification, analysis and descriptive stages. Data validation technique is source triangulation. The results of the study show that the social character education contained in the moral creed book for class V MI contains social care, friendship/communication and peace-loving values.